A study on the surface water movements due to tides off the Kuala Terengganu coast. - Saadon, M.N.; Yaacob, Rosnan
The aim of this study is to understand the effedts of tides surface water movements. The study was conducted in the month April 1989. The area of study is along the coast of Kuala Terengganu to about 4 naut.miles offshore. The Langrangian method is applied where several drogues are deployed at selected stations to track water movements at 1m,3m and 5m belowthe water surface. The drogues are released at 0800 hrs and are allowed to drift for over 8 daylight hours. The positions of the drogues are obtained using a FURUNO Radar installed on board UN1PERTAMA I at every one-hour interval. The results from this study show that the effect of tides on surface water movements near the shore (<0.5 naut.mile) is very significant. At receeding tide the surface water moved northward but at rising tide the reverse occurred. The tide reversed the direction of flow of the surface water near the shore. However, tides has little effect on surface water at 4 naut.miles away from the shore. The water in this region moved northward continuously. The only effect that can be observed on offshore surface water is the reduction in speed and slight alteration in the direction.